Membangun Karakter Anak Usia 0-12 Tahun: Strategi dan Hambatan Orang Tua di Era Digital - Ruth Aty; Handayani Telaumbanua; Aminadab Benu (Sekolah Tinggi Teologi Injili Efrata Sidoarjo, 2025)
Rapid technological developments have had a significant impact on parenting patterns, family interactions, and the formation of children's values ​​and morals. This study aims to analyze the strategies and challenges faced by parents in shaping the character of children aged 0–12 years in the digital era. The research method used was a qualitative approach with a literature review technique. The results showed that the main strategies of parents include the implementation of role-modeling-based parenting, open communication, monitoring device use, and instilling spiritual and social values ​​in daily life. However, parents also face various challenges, including limited time to accompany children, the influence of age-inappropriate digital content, lack of digital literacy, and the gap between family values ​​and the evolving digital culture. This study confirms that the success of children's character formation in the digital era is largely determined by parents' consistency in providing role models, digital literacy skills, and collaboration with the educational environment.